Evaluation of gemtuzumab ozogamycin associated sinusoidal obstructive syndrome: Findings from an academic pharmacovigilance program review and a pharmaceutical sponsored registry. (May 2016) - Magwood-Golston, Jametta S.; Kessler, Samuel; Bennett, Charles L.
Highlights: Gemtuzumab ozogamycin (GO) use is associated with sinusoidal obstructive syndrome (SOS). Academic investigators evaluated SOS from FDA, trials, and case series. The sponsor's registry evaluated GO safety in routine clinical practice. Both sources identified SOS rates higher than the 0.9% reported in licensing trials. Each study's results were disseminated at conferences and in manuscripts. Abstract: Background: In 2000, the Food and Drug Administration (FDA) approved gemtuzumab ozogamycin for monotherapy for older patients with relapsed AML. A 0.9% rate of hepatic sinusoidal obstructive syndrome (SOS) was noted in licensing trials. In 2001, FDA received reports of 14 GO-associated SOS cases from MD Anderson Cancer Center. A State of South Carolina/National Cancer Institute funded pharmacovigilance program and a manufacturer sponsored registry independently evaluated this concern. Methods: The manufacturer's registry and the academic program focused on risk factors and incidence of GO-associated SOS in routine clinical practice and clinical trial settings, respectively. Comparisons were made of findings and dissemination efforts from the two studies. Results: Retrospective analysis of clinical trials by the academic initiative identified 99 cases of SOS among 221 GO-treated stem cell patients and 649 patients who did not undergo HSCTs. SOS rates were 3% when GO was administered at doses ≤6 mg/m 2 as monotherapy or with non-hepatotoxic agents; 28% when administered with 6-thioguanine, a hepatotoxic agent; 15% when administered as monotherapy at doses at a dose of 9 mg/m 2, and between 15% and 40% if a stem cell transplant (SCT) was performed within 3 months of GO administration. Death from SOS occurred in 33% of the cases. The manufacturer's registry prospectively evaluated 482 GO-treated patients who received a mean dose of 7.8 mg/m 2 . Overall, 41% received concomitant chemotherapy, 18% had undergone prior SCT, 9.1% developed SOS, and death from SOS occurred in 60% of the SOS cases. Findings from each initiative were disseminated at national conferences and in peer-reviewed manuscripts beginning in 2003. Conclusion: Retrospective review of clinical trials, case series, and FDA reports and prospective registries can provide important information on safety signals initially identified in licensing trials.